Holocene chironomid-inferred salinity and paleovegetation reconstruction from Kilpoola Lake, British Columbia - Heinrichs, Mark; Walker, Ian; Mathewes, Rolf; Hebda, Richard (Géographie physique et Quaternaire, 1999)
Abstract Salinity fluctuations in lakes of semi-arid regions have been recognised as indicators of paleoclimatic change and have provided a valuable line of evidence in paleoclimatic reconstruction. However, factors other than climate, including sedimentologic events, may also affect salinity. At Kilpoola Lake, early postglacial freshwater chironomids (Microtendipes, Sergentia, and Heterotrissocladius) occur in the basal sediments and yield a chironomid-inferred salinity of <0.03 g/l. Higher salinities, ranging from 1.0 to 3.5 g/l, with Cricotopus/Orthocladius and Tanypus (chironomids typical of saline environments) follow and, persist for most of the remainder of the Holocene. An inferred 450% salinity increase (from 1.6 to 7.3 g/l) occurred in the sediment above the Mount Mazama tephra, followed by a return to the pre-Mount Mazama salinity. The early Holocene pollen spectra are typical of open steppe, but the post-Mazama Artemisia pollen percentages are exceptionally high and are associated with silty clays. Pollen spectra following this Artemisia peak represent steppe communities and are consistent with regional trends. We suggest that the changes in chironomid communities and vegetation after deposition of the Mazama ash do not reflect a rapid shift to warmer or drier climate and evaporation, but rather an increased ionic concentration due to solutes derived from the freshly deposited tephra and perhaps in- washed silts and clays.